2010 5th IEEE International Conference on Global Software Engineering 2010
DOI: 10.1109/icgse.2010.45
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Transfer in IT Offshore Outsourcing Projects: An Analysis of the Current State and Best Practices

Abstract: Knowledge transfer is one of the most critical success factors in IT offshore outsourcing projects and in many cases extremely underestimated. Compared to inhouse or onsite projects, a much higher complexity appears in globally distributed projects. Not only language barriers but also other challenges such as cultural differences, diverse time-zones, distinct methods and approaches, as well as varied infrastructural equipment, may cause problems which negatively impact knowledge transfer, and in consequence, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Many of the selected studies have highlighted ''technological gap'' as one of the major factor that impedes KS [19], [38], [44], [51], [56], [58], [61]. In globally dispersed teams, technological knowledge gaps arise due to difference in experience and educational background.…”
Section: ) Technological Knowledge Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the selected studies have highlighted ''technological gap'' as one of the major factor that impedes KS [19], [38], [44], [51], [56], [58], [61]. In globally dispersed teams, technological knowledge gaps arise due to difference in experience and educational background.…”
Section: ) Technological Knowledge Gapmentioning
confidence: 99%
“…Many studies have found that poor organizational culture negatively influence KS [19], [21], [32], [33], [35], [43], [46], [51], [61]. An unstable organizational structure and hierarchy leads to flaws in proper KS.…”
Section: Organizational Barriers 1) Poor Organizational Culturementioning
confidence: 99%
“…Knowledge transfer has been studied in a variety of business and governmental settings, including political alliances, joint ventures, independent firms, and mergers and acquisitions [14,22]. However, our literature review revealed that only a few researchers [e.g.…”
Section: Related Conceptsmentioning
confidence: 99%
“…While several scholars have studied structured knowledge transfer [8,14], only a few have investigated unstructured knowledge transfer [15]. Thus, in this research we explore the complexities of unstructured knowledge transfer in offshore outsourced software development (OOSD) projects, with a particular focus on the challenges faced by SMEs.…”
Section: Introductionmentioning
confidence: 99%
“…But there is a need to understand that why some services are produced in house and why others are contracted out [4]. Client organizations outsource their work offshore when they expect the market to be more cost efficient or when they believe skills, knowledge or experience are available via the market that are not available in-house [5]. OSDO is not a risk free business; however it also drew tending due to complexity and high quality software development.…”
Section: Introductionmentioning
confidence: 99%